Changing the Total Allowable Catch (TAC) Decision-Making Framework: A Central Bank of Fishes? - Astorkiza, Kepa; del Valle, Ikerne (Panoeconomicus, 2013)
The difficulties that the current model of TAC regulation generates in the current system of EU fisheries are analysed. Although the production structure of the TAC has been set up in collaboration with ICES, the determination process lacks short-term contributions from the field of biology. Once these inputs undergo the decision process of the EU, the resulting TACs are significantly biased in relation to the initial recommendations. To solve this problem, a different institutional model with the addition of a Central Bank-like of Fishes is proposed. Key words: Common Fisheries Policy (CFP), Individual Transferable Quota (ITQ), European Union (EU), Central Bank-like of Fishes (CBF), International Council for the Exploration of the Sea (ICES). JEL: Q22, H12, L16, K23.